2022
DOI: 10.3389/fpubh.2022.1003178
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory-based surveillance of antimicrobial resistance in regions of Kenya: An assessment of capacities, practices, and barriers by means of multi-facility survey

Abstract: BackgroundAdequate laboratory capacity is critical in the implementation of coherent surveillance for antimicrobial resistance (AMR). We describe capacities and deficiencies in laboratory infrastructure and AMR surveillance practices among health facilities in Kenya to support progress toward broader sustainable laboratory-based AMR surveillance.MethodsA convenience sample of health facilities from both public and private sectors across the country were selected. Information was obtained cross-sectionally betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 23 publications
4
9
1
Order By: Relevance
“…Our findings are evidenced by the low overall score regarding the indicators used in assessing the capacity of laboratories to test for AMR and perform all bacteriological processes. These findings align with those reported in other studies [6,61,62]. A recent study conducted in Zambia in secondary and tertiary hospitals found an overall capacity of 52%, with the highest-scoring hospital having scored 63% and the lowest having scored 38% [63].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings are evidenced by the low overall score regarding the indicators used in assessing the capacity of laboratories to test for AMR and perform all bacteriological processes. These findings align with those reported in other studies [6,61,62]. A recent study conducted in Zambia in secondary and tertiary hospitals found an overall capacity of 52%, with the highest-scoring hospital having scored 63% and the lowest having scored 38% [63].…”
Section: Discussionsupporting
confidence: 91%
“…Our findings resonate with another study conducted in Ethiopia where, despite the availability of laboratories, there was a lack of basic equipment and consumables to conduct AMR testing [6]. Another study in Kenya reported similar findings where nearly one-third of the healthcare facilities examined did not offer bacterial culture testing, and only [61]. This was due to poor access to LIS, low participation in external quality assessment programs for cultures, severe infrastructural gaps and lack of equipment [61].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Of those sampled, the majority of facilities ( n = 135, 61%) did not perform bacterial culture testing, and even fewer performed antimicrobial susceptible testing ( n = 37, 17%). 12 …”
Section: Methodsmentioning
confidence: 99%
“…The inadequacy of laboratory infrastructure, especially in rural areas where basic requirements are rarely met, poses a significant barrier to reliable pathogen detection and AST [ 8 ]. Moreover, there exists a persistent healthcare delivery imbalance across counties, with over twice the laboratory technology accessibility in urban areas compared to their rural counterparts in Kenya [ 19 ].…”
Section: Drivers Of Antibiotic Resistancementioning
confidence: 99%